PENGARUH PAJAK DAERAH, JUMLAH PENDUDUK, PENGELUARAN PEMERINTAH DAN INVESTASI TERHADAP PENDAPATAN ASLI DAERAH DI PROVINSI BANTEN - Rifky Ramadhani (2022)
Regional Original Income (PAD) is one of the sources of budget owned by regions that are used to exercise regional autonomy with the aim of providing welfare to the community in a fair and equitable manner. This study was conducted to determine the effect of local taxes, population, government expenditure, and investment on Regional Original Income (PAD). This study used all regencies/cities in Banten Province. Sample determination using sampling technique is saturated with 8 regions during 2016-2020, then the total sample is 40. The data used is secondary data obtained from the Central Statistics Agency, the Directorate General of Financial Balance (DJPK) of the Ministry of Finance, and the Investment Coordinating Board. Hypothesis testing in this study used Panel Data Analysis with the Eviews 10 program and a significance level of 5% (0.05). The results of the study partially showed that local taxes affect PAD, the number of people affects PAD, while government expenditure, and investment do not affect PAD.